2024
DOI: 10.1126/science.adj5763
|View full text |Cite
|
Sign up to set email alerts
|

Climate change is an important predictor of extinction risk on macroevolutionary timescales

Cooper M. Malanoski,
Alex Farnsworth,
Daniel J. Lunt
et al.

Abstract: Anthropogenic climate change is increasing rapidly and already impacting biodiversity. Despite its importance in future projections, understanding of the underlying mechanisms by which climate mediates extinction remains limited. We present an integrated approach examining the role of intrinsic traits versus extrinsic climate change in mediating extinction risk for marine invertebrates over the past 485 million years. We found that a combination of physiological traits and the magnitude of climate change is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 110 publications
0
2
0
1
Order By: Relevance
“…This admittedly coarse estimate for a lineage of modern moss taxa is nevertheless in line with estimates of the beginnings of the evolution of the modern moss flora. According to Bechteler et al [ 3 ], extant bryophyte families diversified across the Cretaceous and early Cenozoic, with the majority occurring during the Cretaceous terrestrial revolution, while climate fluctuations [ 29 , 30 ] during this time encouraged the diversification of bryophytes in arid (Pottiaceae) and exposed (Funariaceae) lands. Jauregui-Lazo et al [ 31 ] reported in a molecular study the age of the Syntrichia (Pottiaceae) lineage as 50.1 ± 6.3 mya (early Eocene) with a recent diversification at 15–12 mya, and they further estimated that Streptotrichaceae (as Leptodontium capituligerum and L. pungens ) broke from the stem Pottiaceae at about 120 mya.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This admittedly coarse estimate for a lineage of modern moss taxa is nevertheless in line with estimates of the beginnings of the evolution of the modern moss flora. According to Bechteler et al [ 3 ], extant bryophyte families diversified across the Cretaceous and early Cenozoic, with the majority occurring during the Cretaceous terrestrial revolution, while climate fluctuations [ 29 , 30 ] during this time encouraged the diversification of bryophytes in arid (Pottiaceae) and exposed (Funariaceae) lands. Jauregui-Lazo et al [ 31 ] reported in a molecular study the age of the Syntrichia (Pottiaceae) lineage as 50.1 ± 6.3 mya (early Eocene) with a recent diversification at 15–12 mya, and they further estimated that Streptotrichaceae (as Leptodontium capituligerum and L. pungens ) broke from the stem Pottiaceae at about 120 mya.…”
Section: Resultsmentioning
confidence: 99%
“…All lineages of modern bryoflora that are more than four microgenera in depth probably reach back in time to the Cretaceous–Paleocene boundary of 66 mya or beyond. During the past 100 my, lineages with extant species have adapted to major environmental perturbations [ 29 , 30 ] by physiological and morphological adaptations, migrating, switching substrates, and other strategies now in part engraved in their ancestrons. Temperatures today average 14–16 °C, with diurnal variation of about 15 °C, ranging from 8 °C (temperate cities, tropical forests) to 40 °C (highland deserts), while tropical areas today range from 18 to 30 °C [ 35 ] (p. 91).…”
Section: Discussionmentioning
confidence: 99%
“…然而, 因为可利用的指标有限, 这些物种分布模型 通常基于有限的生物耐受性指标(如温度升高造成的 海水氧气含量降低), 但往往忽略扩散能力和扩散时间 以及生物相互作用等生物自身因素 [99,109,113] , 此外, 古 环境模型同样往往基于过度简化的边界条件, 以便更 高效地进行因子平衡的模拟 [98] , 并且其依据的古地理 模型本身也具有一定的不确定性, 这就使得生态模型 的两大基础: 古地理和古环境的可信度也均有待于进 一步完善.…”
Section: 时间演变模式unclassified